Courses
Courses for Kids
Free study material
Offline Centres
More

How do you solve \[{x^2} - 2x = - 2\] ?

seo-qna
Last updated date: 26th Feb 2024
Total views: 340.5k
Views today: 10.40k
IVSAT 2024
Answer
VerifiedVerified
340.5k+ views
Hint: If we have a polynomial of degree ‘n’ then we have ‘n’ number of roots or factors. A polynomial of degree two is called a quadratic polynomial and its zeros can be found using many methods like factorization, completing the square, graphs, quadratic formula etc. The quadratic formula is used when we fail to find the factors of the equation. In the given question we have to solve the given quadratic equation using the quadratic formula. That is \[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\].

Complete step by step answer:
Given, \[{x^2} - 2x = - 2\]. We need to write this in standard form of \[a{x^2} + bx + c = 0\].
Transposing -2 to the left side of the equation by adding 2 on the left hand side of the equation.
\[{x^2} - 2x + 2 = 0\]
On comparing the given equation with the standard quadratic equation \[a{x^2} + bx + c = 0\]. We get, \[a = 1\], \[b = - 2\] and \[c = 2\].
Substituting in the formula of standard quadratic,
\[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
\[ \Rightarrow x = \dfrac{{ - ( - 2) \pm \sqrt {{{( - 2)}^2} - 4(1)(2)} }}{{2(1)}}\]
\[ \Rightarrow x = \dfrac{{2 \pm \sqrt {4 - 8} }}{2}\]
\[ \Rightarrow x = \dfrac{{2 \pm \sqrt { - 4} }}{2}\]
\[ \Rightarrow x = \dfrac{{2 \pm i\sqrt 4 }}{2}\]
\[ \Rightarrow x = \dfrac{{2 \pm i2}}{2}\]
Taking ‘2’ common we have,
\[ \Rightarrow x = \dfrac{{2(1 \pm i)}}{2}\]
\[ \therefore x = 1 \pm i\]

Thus we have two roots, \[x = 1 + i\] and \[x = 1 - i\].

Note:In various fields of mathematics require the point at which the value of a polynomial is zero, those values are called the factors/solution/zeros of the given polynomial. On the x-axis, the value of y is zero so the roots of an equation are the points on the x-axis that is the roots are simply the x-intercepts. We cannot solve this by simple factorization. That is by expanding the middle term into sum of two terms, such the product of two terms is equal to product of ‘a’ and ‘c’, sum of two terms is equal to ‘b’ (Comparing with \[a{x^2} + bx + c = 0\]) . We also know that the quadratic formula is also known as Sridhar’s formula.
Recently Updated Pages